Role of Extracts Obtained from Rainbow Trout and Sole Side Streams by Accelerated Solvent Extraction and Pulsed Electric Fields on Modulating Bacterial and Anti-Inflammatory Activities - Min Wang; Jianjun Zhou; Noelia Pallarés; Christine Bäuerl; Maria Carmen Collado; Basharat Nabi Dar; Francisco J. Barba (Separations, 2021)
In this study, accelerated solvent extraction (ASE) and pulsed electric field (PEF) were used as innovative approaches to recover extracts from rainbow trout and sole side streams rich in high-added-value compounds. Then, after aseptic filtration, the impact of the obtained extracts on bacterial growth and anti-inflammatory potential was evaluated. Moreover, the protein content and the total antioxidant capacity of the samples were determined. The results showed that some extracts could inhibit the growth of pathogenic bacteria, including the ASE rainbow trout skin and the PEF sole viscera extracts, which showed significant antibacterial activity on Staphylococcus aureus. The PEF sole viscera extract also showed an inhibitory effect on the growth of Salmonella. In addition, some extracts promoted probiotic bacteria growth. For example, the PEF rainbow trout head and skin extracts promoted Lactobacillus casei growth, while the ASE rainbow trout head and skin extracts promoted Bifidobacterium lactis growth. In addition, some samples, such as the ASE rainbow trout viscera and the PEF sole skin extracts had interesting anti-inflammatory properties. Therefore, the use of ASE and PEF can be considered as useful strategies to recover antimicrobial, prebiotic and anti-inflammatory extracts from rainbow trout and sole side streams, although it is necessary to evaluate each specific side stream.